Home My Page Projects Code Snippets Project Openings diderot
Summary Activity Tracker Tasks SCM

SCM Repository

[diderot] Diff of /branches/ein16/src/compiler/high-il/normalize-ein.sml
ViewVC logotype

Diff of /branches/ein16/src/compiler/high-il/normalize-ein.sml

Parent Directory Parent Directory | Revision Log Revision Log | View Patch Patch

revision 2485, Mon Oct 21 16:34:57 2013 UTC revision 2499, Mon Nov 4 16:10:36 2013 UTC
# Line 47  Line 47 
47          (* end case *)          (* end case *)
48           end           end
49    
50    (* filter function shifts constant/greeks to outside product*)
51    fun filter([],pre,post)=(pre,post)
52        | filter(E.Const c::es, pre, post)=filter(es, pre@[E.Const c],post)
53        | filter(E.Delta d::es,pre,post)=filter(es,pre@[E.Delta d],post)
54        | filter(E.Value v::es, pre, post)=filter(es, pre@[E.Value v],post)
55        | filter(E.Epsilon e::es, pre, post)=filter(es, pre@[E.Epsilon e],post)
56        | filter(E.Tensor(id,[])::es, pre, post)=filter(es, pre@[E.Tensor(id,[])],post)
57        | filter(E.Prod p::es, pre, post)=filter(p@es,pre,post)
58        | filter(e::es, pre, post)= filter(es, pre, post@[e])
59    
60    
61    
62  fun rmEpsIndex(_,_,[])=[]  fun prodPartial ([e1],p1)= E.Prod[E.Partial p1,e1]
63  | rmEpsIndex([],[],cs)=cs    | prodPartial((e1::e2),p1)=let
64  | rmEpsIndex([],m ,e1::cs)=[e1]@rmEpsIndex(m,[],cs)      val l= prodPartial(e2,p1)
65  | rmEpsIndex(i::ix,rest ,(E.V c)::cs)=      val (_,e2')= mkProd[e1,l]
66      if(i=c) then rmEpsIndex(rest@ix,[],cs)      val (_,e1')=mkProd(e2@ [E.Partial p1, e1])
67      else rmEpsIndex(ix,rest@[i],(E.V c)::cs)      in
68            E.Add[e1',e2']
69        end
70    
71    fun prodAppPartial ([e1],p1)= E.Apply(E.Partial p1,e1)
72      | prodAppPartial((e1::e2),p1)=let
73        val l= prodAppPartial(e2,p1)
74        val (_,e2')= mkProd[e1,l]
75        val (_,e1')=mkProd(e2@ [E.Apply(E.Partial p1, e1)])
76        in
77            E.Add[e1',e2']
78        end
79    
80    
81    
82    
83    (*remove eps Index*)
84    fun rmEpsIndex(i,[],rest)=rest
85      | rmEpsIndex(i, (E.V c ,lb, ub)::es,rest)=
86        if (i=c) then rest@es
87        else rmEpsIndex(i, es, rest@[(E.V c, lb, ub)])
88    
89    
90    (*remove index variable from list*)
91    fun rmIndex(_,_,[])=[]
92        | rmIndex([],[],cs)=cs
93        | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
94        | rmIndex(i::ix,rest ,(c,lb,ub)::cs)=
95            if(i=c) then rmIndex(rest@ix,[],cs)
96            else rmIndex(ix,rest@[i],(c,lb,ub)::cs)
97    
98    
99    
100    
101  (* Transform eps to deltas*)  (* Transform eps to deltas*)
# Line 68  Line 108 
108    
109              (*remove index from original index list*)              (*remove index from original index list*)
110    
111              val s'= rmEpsIndex([i,s,t,u,v],[],count)              val s'= rmEpsIndex(i,count,[])
112              val s''=[E.V s, E.V t ,E.V u, E.V v]  
113              val deltas= E.Sub(              val deltas= E.Sub(
114                      E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),                      E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3),
115                      E.Sum(s'',E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3)))                      E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3))
116    
117                  in (case (eps,es,s')                  in (case (eps,es,s')
118                  of ([],[],[]) =>(1,deltas)                  of ([],[],[]) =>(1,deltas)
# Line 109  Line 149 
149          end          end
150    
151      val (es,rest)=findeps([],e)      val (es,rest)=findeps([],e)
   
152      in      in
153          dist(es,[],rest)          dist(es,[],rest)
154      end      end
155    
156    
 fun rmIndex(_,_,[])=[]  
     | rmIndex([],[],cs)=cs  
     | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)  
     | rmIndex(i::ix,rest ,c::cs)=  
         if(i=c) then rmIndex(rest@ix,[],cs)  
         else rmIndex(ix,rest@[i],c::cs)  
157    
158  (* Apply deltas to tensors/fields*)  (* Apply deltas to tensors/fields*)
159  fun reduceDelta(E.Sum(c,E.Prod p))=let  fun reduceDelta(E.Sum(c,E.Prod p))=let
# Line 129  Line 162 
162      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
163      | findDeltas(dels,rest,es)=  (dels,rest,es)      | findDeltas(dels,rest,es)=  (dels,rest,es)
164    
   
165      fun distribute(change,d,dels,[],done)=(change,dels@d,done)      fun distribute(change,d,dels,[],done)=(change,dels@d,done)
166      | distribute(change,[],[],e,done)=(change,[],done@e)      | distribute(change,[],[],e,done)=(change,[],done@e)
167      | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=      | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
# Line 145  Line 177 
177      val index=rmIndex(change,[],c)      val index=rmIndex(change,[],c)
178    
179    in    in
180         (change, E.Sum(index,E.Prod (eps@dels'@done)))         (length change, E.Sum(index,E.Prod (eps@dels'@done)))
181    end    end
182    
183    
184  fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(print "apply sum";case e  (*Apply Sum*)
185    fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(case e
186      of E.Tensor(a,[])=>(1,E.Const 0.0)      of E.Tensor(a,[])=>(1,E.Const 0.0)
187      | E.Const _ =>(1,E.Const 0.0)      | E.Const _ =>(1,E.Const 0.0)
188        | E.Delta _ =>(1,E.Const 0.0)
189        | E.Value _ =>(1,E.Const 0.0)
190        | E.Epsilon _ =>(1,E.Const 0.0)
191    
192      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))
193      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))
194        | E.Conv (fid,alpha,tid, delta)=> let
195            val e'=E.Conv(fid,alpha, tid, delta@d)
196            in (1,E.Sum(c,e')) end
197      | E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))      | E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))
198      | E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,e1))])      | E.Prod es=> let
199            val (pre, post)= filter(es,[],[])
200      | E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,E.Prod e2))])          val x1= prodAppPartial(post,d)
201            in  (case x1
202      | E.Prod es=>(let                  of E.Add a=> (1,E.Add(List.map (fn e =>  E.Sum(c,E.Prod(pre@[e]))) a))
203          fun prod [e1] =E.Apply(E.Partial d,e1)                  | _ => (1,E.Sum(c, E.Prod(pre@[x1])))
204          | prod (E.Epsilon eps1::es) = (E.Apply(E.Partial d, E.Prod (E.Epsilon eps1::es)))              (*end case*))
205          | prod (E.Delta e1::es) = (E.Apply(E.Partial d, E.Prod (E.Delta e1::es)))          end
         | prod (E.Prod e1::es)=prod(e1@es)  
         | prod(e1::e2)=(let  
             val l= prod(e2)  
             val (_, a)= mkProd[e1,l]  
             val lr=e2 @[E.Apply(E.Partial d,e1)]  
             val(_,b) =mkProd lr  
             in  E.Add[b,a]  
             end)  
         val chainrule=prod es  
         in (1,E.Sum(c, chainrule)) end)  
206      |_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))      |_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))
207      (* end case*))      (* end case*))
208    
209  fun mkApply2(E.Apply(E.Partial d,e))=(print "aa";case e  (*Apply*)
210    fun mkApply(E.Apply(E.Partial d,e))=(case e
211      of E.Tensor(a,[])=>(1,E.Const 0.0)      of E.Tensor(a,[])=>(1,E.Const 0.0)
212      | E.Const _ =>(1,E.Const 0.0)      | E.Const _ =>(1,E.Const 0.0)
213        | E.Delta _ =>(1,E.Const 0.0)
214        | E.Value _ =>(1,E.Const 0.0)
215        | E.Epsilon _ =>(1,E.Const 0.0)
216        | E.Conv (fid,alpha,tid, delta)=> let
217            val e'=E.Conv(fid,alpha, tid, delta@d)
218            in (1,e') end
219      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
220      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
221      | E.Apply(E.Partial e1,e2)=>(1,E.Apply(E.Partial(d@e1), e2))      | E.Div(e2, e3) =>(1, E.Div(E.Apply(E.Partial d, e2),  e3))
222        | E.Apply(E.Partial d2,e2)=>(1,E.Apply(E.Partial(d@d2), e2))
223      | E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))      | E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
224      | E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,e1)])      | E.Prod es=> let
225      | E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Prod e2)])          val (pre, post)= filter(es,[],[])
226      | E.Prod es=> (let          val (_,x)=mkProd(pre@[prodAppPartial(post,d)])
227          fun prod [e1] =(0,E.Apply(E.Partial d,e1))          in (1,x) end
228          | prod (E.Epsilon eps1::es) = (0,E.Apply(E.Partial d, E.Prod (E.Epsilon eps1::es)))      |_=>(0,E.Apply(E.Partial d,e))
229          | prod (E.Delta e1::es) = (0,E.Apply(E.Partial d, E.Prod (E.Delta e1::es)))      (* end case*))
          | prod (E.Prod e1::es)=prod(e1@es)  
         | prod(E.Tensor t::e2)=(let  
             val (_,l)= prod(e2) val m= E.Prod[E.Tensor t,l]  
             val lr=e2 @[E.Apply(E.Partial d,E.Tensor t)] val(b,a) =mkProd lr  
             in  (1,E.Add[a,m])  
             end)  
         | prod(E.Field f::e2)=(let  
             val (_,l)= prod(e2) val m= E.Prod[E.Field f,l]  
             val lr=e2 @[E.Apply(E.Partial d,E.Field f)] val(b,a) =mkProd lr  
             in  (1,E.Add[a,m])  
             end)  
         | prod e = (0,E.Apply(E.Partial d, E.Prod e))  
230    
231    (*Sum Apply*)
232    
         val (a,b)= prod es  
233    
234          in (a, b) end)  fun mkSumApply(E.Sum(c,E.Apply(E.Partial d,e)))=(case e
235      |_=>(0,E.Apply(E.Partial d,e))  
     (* end case*))  
236    
 fun mkSumApply2(E.Sum(c,E.Apply(E.Partial d,e)))=(print "in here ";case e  
237      of E.Const _=>(1,E.Const 0.0)      of E.Const _=>(1,E.Const 0.0)
238      | E.Tensor(_,[])=> (1,E.Const 0.0)      | E.Tensor(_,[])=> (1,E.Const 0.0)
239      | E.Field _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))      | E.Delta _ =>(1,E.Const 0.0)
240      | E.Apply(E.Partial e1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@e1),e2)))      | E.Value _ =>(1,E.Const 0.0)
241        | E.Epsilon _ =>(1,E.Const 0.0)
242        | E.Conv (fid,alpha,tid, delta)=> let
243            val e'=E.Conv(fid,alpha, tid, delta@d)
244            in (1,E.Sum(c,e')) end
245        | E.Apply(E.Partial d1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@d1),e2)))
246      | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))      | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
247      | E.Sub(e2, e3) =>      | E.Sub(e1, e2) => (1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e1)), E.Sum(c,E.Apply(E.Partial d, e2))))
                 (*(0,E.Sub(e2,e3))  
                 *)  
                 (print "sub";(1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e2)), E.Sum(c,E.Apply(E.Partial d, e3)))))  
   
      | E.Prod [e1]=>(print "one";(1,E.Sum(c,E.Apply(E.Partial d,e1))))  
248    
249        | E.Prod [e1]=>(1,E.Sum(c,E.Apply(E.Partial d,e1)))
250    
     | E.Prod(E.Tensor(a,[])::e2::[])=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,e2))]))  
251    
252      | E.Prod(E.Tensor(a,[])::e2)=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))]))      | E.Prod(E.Tensor(a,[])::e2)=>(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))])
253    
254      | E.Prod es =>(print "in prod";let      | E.Prod es =>(let
255          fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))          fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
256          | prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let          | prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
257              fun matchprod(2,_,_,_)= 1 (*matched 2*)              fun matchprod(2,_,_,_)= 1 (*matched 2*)
# Line 265  Line 287 
287    
288          | prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)          | prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)
289    
290          val (change,exp) = prod(0,[],c, d, es)          in  prod(0,[],c, d, es)
291    
292    
         in  
             (change,exp)  
293          end)          end)
294          | _=>(print "nope";(0,E.Sum(c,E.Apply(E.Partial d,e))))          | _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))
295          (* end case*))          (* end case*))
296    
 (*  
 E.Sum(c,Apply(d,e))  
     try E.Sum(c,e)=> E.Sum(c',e')  
     ==>    E.Sum(c',E.Apply(d,e'))  
         E.Apply(d,e')=> E.Apply(d',e'')  
     ==>E.Sum(c',E.Apply(d',e'')  
 *)  
297    
298  (*Apply normalize to each term in product list  (*Apply normalize to each term in product list
299  or Apply normalize to tail of each list*)  or Apply normalize to tail of each list*)
# Line 291  Line 305 
305               of E.Const _=> body               of E.Const _=> body
306                | E.Tensor _ =>body                | E.Tensor _ =>body
307                | E.Field _=> body                | E.Field _=> body
               | E.Krn _ =>body  
308                | E.Delta _ => body                | E.Delta _ => body
309                | E.Value _ =>body                | E.Value _ =>body
310                | E.Epsilon _=>body                | E.Epsilon _=>body
311                  | E.Conv _=>body
312    
313                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
314                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)
# Line 302  Line 316 
316                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
317                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
318                | E.Partial _=>body                | E.Partial _=>body
319                | E.Conv (V, alpha)=> E.Conv(rewriteBody V, alpha)                | E.Krn(tid,deltas,pos)=> E.Krn(tid,deltas, (rewriteBody pos))
320                | E.Probe(u,v)=>  E.Probe(rewriteBody u, rewriteBody v)                | E.Img(fid,alpha,pos)=> E.Img(fid,alpha, (List.map rewriteBody pos))
321                | E.Img _ => body  
322    
323                  (*Product*)                  (*************Product**************)
324                | E.Prod [e1] => rewriteBody e1                | E.Prod [e1] => rewriteBody e1
325                | E.Prod(e1::(E.Add(e2))::e3)=>                | E.Prod((E.Add(e2))::e3)=>
326                       (changed := true; E.Add(List.map (fn e=> E.Prod([e]@e3)) e2))
327                  | E.Prod((E.Sub(e2,e3))::e4)=>
328                       (changed :=true; E.Sub(E.Prod([e2]@e4), E.Prod([e3]@e4 )))
329    
330                  | E.Prod((E.Div(e2,e3))::e4)=>
331                    (changed :=true; E.Div(E.Prod([e2]@e4), e3 ))
332    
333                  | E.Prod(e1::E.Add(e2)::e3)=>
334                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))
335                | E.Prod(e1::(E.Sub(e2,e3))::e4)=>                | E.Prod(e1::E.Sub(e2,e3)::e4)=>
336                     (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))                     (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))
337                | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>  
338                     (changed:=true;E.Conv(f,deltas@r1))  
339                | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>  
340                     (changed:=true;  
                     let val (change,e)=mkProd([E.Conv(f,deltas@r1)]@ps)  
                     in e end)  
341                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
342                      if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))                      if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))
343                      else body                      else body
344               | E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))               | E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))
345                  | E.Prod [E.Partial r1,E.Partial r2]=>
346                    (changed:=true;E.Partial(r1@r2))
347    
348               | E.Prod(E.Partial r1::E.Partial r2::p)=>               | E.Prod(E.Partial r1::E.Partial r2::p)=>
349                     (changed:=true;E.Prod([E.Partial(r1@r2)]@p))                     (changed:=true;E.Prod([E.Partial(r1@r2)]@p))
              | E.Prod [E.Partial _, _] =>body  
   
              | E.Prod (E.Partial p1::es)=> (let  
                 fun prod [e1] =E.Apply(E.Partial p1,e1)  
                 | prod(e1::e2)=(let  
                     val l= prod(e2) val m= E.Prod[e1,l]  
                     val lr=e2 @[E.Apply(E.Partial p1,e1)] val(b,a) =mkProd lr  
                     in  E.Add[a,m]  
                     end)  
                 in (changed:=true;prod es) end)  
   
350                | E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es)=>let                | E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es)=>let
351                    val (change,e,rest)=epsToDels(E.Sum(c1@c2, E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es)))                    val (change,e,rest)=epsToDels(E.Sum(c1@c2, E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es)))
352                    in(case (change,e, rest)                    in(case (change,e, rest)
353                      of (1,[e1],_)=> e1                      of (1,[e1],_)=> (changed:=true;e1)
354                      | _=>body)                      | _=>let
355                            val e1=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))
356                            val es'=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
357                            val (_,e)=(case es' of E.Prod p=>mkProd([e1]@p)
358                                |_=> mkProd([e1]@e)
359                                (*end case*))
360                            in e
361                  end                  end
362                        (*end case*))
363                    end
364                  | E.Prod[e1,e2]=> body
365                | E.Prod(e::es)=>let                | E.Prod(e::es)=>let
366                      val e'=rewriteBody e                      val e'=rewriteBody e
367                      val e2=rewriteBody(E.Prod es)                      val e2=rewriteBody(E.Prod es)
368                      val(a,b)=(case e2 of E.Prod p'=> mkProd([e']@p')                      val(_,b)=(case e2
369                            of E.Prod p'=> mkProd([e']@p')
370                          |_=>mkProd [e',e2])                          |_=>mkProd [e',e2])
371                      in b                      in b
372                     end                     end
373    
374                (*Apply*)                (**************Apply**************)
375    
376                | E.Apply(E.Partial d,E.Sum(c,e))=>let                (* Apply, Sum*)
377                      val(c,e')=mkApplySum(E.Apply(E.Partial d,E.Sum(c, rewriteBody e)))                | E.Apply(E.Partial d,E.Sum e)=>let
378                      val e''=(case e'                      val s'=rewriteBody(E.Sum  e)
379                          of E.Apply(d,E.Sum s)=>E.Apply(d,rewriteBody(E.Sum s))                      val (c, e')=(case s'
380                          |_=> e')                          of E.Sum e1=> mkApplySum(E.Apply(E.Partial d,s'))
381                  in (print "bb";case c of 1=>(changed:=true;e'')                          | _=>(0, E.Apply(E.Partial d, s'))
382                      |_=> e'')end                          (*end case*))
383                | E.Apply(E.Partial [],e)=> e                      in (case c
384                            of 1=>(changed:=true;e')
385                            |_=> e'
386                        (*end case*))
387                        end
388    
389                  | E.Apply(E.Partial [],e)=> e
390                  | E.Apply(E.Partial p,E.Probe(E.Conv(fid,alpha,tid,d),x))=>
391                    (changed:=true;E.Probe(E.Conv(fid,alpha,tid,d@p),x))
392                  | E.Apply(E.Partial p,E.Conv(fid,alpha,tid,d))=>
393                    (changed:=true;E.Conv(fid,alpha,tid,d@p))
394                | E.Apply(E.Partial p, e)=>let                | E.Apply(E.Partial p, e)=>let
395    
396                      val body'=E.Apply(E.Partial p, rewriteBody e)                      val body'=E.Apply(E.Partial p, rewriteBody e)
397                      val (c, e')=mkApply2(body')                          val (c, e')=mkApply(body')
398                  in (case c of 1=>(changed:=true;e')                      in (case c
399                            of 1=>(changed:=true;e')
400                      | _ =>e') end                      | _ =>e') end
               | E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)  
401    
402                    | E.Apply(e1,e2)=>((E.Apply(rewriteBody e1, rewriteBody e2))
403                       )
404    
405    
406                (* Sum *)                (************** Sum *****************)
407                | E.Sum([],e)=> (changed:=true;rewriteBody e)                | E.Sum([],e)=> (changed:=true;rewriteBody e)
408                | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)                | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
409                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))
410                | E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))                | E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))
411                  | E.Sum(c,E.Div(e1,e2))=>(changed:=true; E.Div(E.Sum(c,e1),E.Sum(c,e2)))
412                  | E.Sum(c, E.Prod(E.Const e::es))=>(changed:=true;E.Prod[E.Const e,E.Sum(c, E.Prod es)])
413    
414                  | E.Sum(c, E.Prod(E.Value v::es))=>(changed:=true; E.Prod [E.Value v, E.Sum(c, E.Prod es)])
415                  | E.Sum(c, E.Prod(E.Tensor(id,[])::es))=> (changed:=true;E.Prod [E.Tensor(id,[]), E.Sum(c, E.Prod es)])
416                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
417                     let val (i,e,rest)=epsToDels(body)                     let val (i,e,rest)=epsToDels(body)
418                  in (print "eps to dels \n ";case (i, e,rest)                  in (case (i, e,rest)
419                  of (1,[e1],r) =>(print "changed\n";changed:=true;e1)                      of (1,[e1],r) =>(changed:=true;e1)
420                  |(0,eps,[])=>(print "non";body)                      |(0,eps,[])=>body
421                          |(0,eps,rest)=>(let                      |(0,eps,rest)=> let
422                              val p'=rewriteBody(E.Prod rest)                              val p'=rewriteBody(E.Prod rest)
423                              val p''= (case p' of E.Prod p=>p |e=>[e])                              val p''= (case p' of E.Prod p=>p |e=>[e])
424                              val(a,b)= mkProd (eps@p'')                          val(_,b)= mkProd (eps@p'')
425                              in E.Sum(c,b) end                              in E.Sum(c,b) end
426                              )                      |_=>body
427                          |_=>body)                      (*end case*))
428                     end                     end
429    
430                | E.Sum(c1,E.Prod(E.Epsilon eps1::E.Sum(c2,E.Prod(E.Epsilon eps2::s2))::ps))=>let                | E.Sum(c1,E.Prod(E.Epsilon eps1::E.Sum(c2,E.Prod(E.Epsilon eps2::s2))::ps))=>let
# Line 399  Line 437 
437    
438                | E.Sum(c, E.Prod(E.Delta d::es))=>let                | E.Sum(c, E.Prod(E.Delta d::es))=>let
439                      val (change,a)=reduceDelta(body)                      val (change,a)=reduceDelta(body)
440                      val (change',body')=(case a                      in (case (change,a)
441                          of E.Prod p=> mkProd p                  of (0, _)=> E.Sum(c,rewriteBody(E.Prod([E.Delta d]@es)))
442                          |_=> (0,a))                          | (_, E.Prod p)=>let
443                     in (case change of []=>body'|_=>(changed:=true;body')) end                              val (_, p') = mkProd p
444                                in (changed:=true;p') end
445                | E.Sum(c,E.Apply(E.Partial _,e))=>let                          | _ => (changed:=true;a )
446                      val (change,exp)=mkSumApply2(body)                          (*end case*))
447                      val exp'=(case exp                      end
                         of  E.Const c => E.Const c  
                         | E.Sum(c',E.Apply(d',e'))  => (let  
                             val s'=rewriteBody(E.Sum(c',e'))  
                            in (case s'  
                                 of E.Sum([],e'')=> rewriteBody (E.Apply(d',e''))  
                                 | E.Sum(s'',e'') => E.Sum(s'',rewriteBody(E.Apply(d',e'')))  
                                 | _ => E.Apply(d',s'))  
448    
                             end)  
449    
450                  | E.Sum(c,E.Apply(E.Partial p,e))=>let
451                        val (change,exp)=mkSumApply(body)
452                        val exp'=(case change
453                            of 1=> (changed:=true;exp)
454                            | _ => E.Sum(c,rewriteBody(E.Apply(E.Partial p,e))))
455                        in exp' end
456    
                         | _ =>exp  
                         (* end case *))  
457    
458                  in (case change of 1=>(changed:=true;exp') |_=>exp')                  | E.Sum(c,e)=>E.Sum(c,rewriteBody e)
                 end  
459    
460                (*Probe*)
461                | E.Probe(E.Sum(c,s),x)=>(changed:=true;E.Sum(c,E.Probe(s,x)))
462                | E.Probe(E.Neg e1,x)=>(changed:=true;E.Neg(E.Probe(e1,x)))
463                | E.Probe(E.Add es,x) =>
464                    (changed:=true;E.Add(List.map (fn(e1)=>E.Probe(e1,x)) es))
465                | E.Probe(E.Sub (a,b),x)=>
466                    (changed:=true;E.Sub(rewriteBody(E.Probe(a,x)), rewriteBody(E.Probe(b,x))))
467                | E.Probe(E.Div (a,b),x) =>
468                    (changed:=true;E.Div(rewriteBody(E.Probe(a, x)),b))
469    
               | E.Sum(c,e)=>E.Sum(c,rewriteBody e)  
470    
471    
472                    (*
473                    | E.Probe(E.Prod([E.Sum s] @es),x)
474                    | E.Probe(E.Prod([E.Neg e] @es),x)
475                      | E.Probe(E.Prod([E.Apply e] @es),x) needs to be rewritten
476                    *)
477    
478    
479                (*Should be taken care of in next rule.
480                | E.Probe(E.Prod([E.Add e] @es),x)
481                | E.Probe(E.Prod([E.Sub (e1,e2)] @es),x)=>
482                | E.Probe(E.Prod([E.Div e] @es),x)=>
483                *)
484    
485    
486    
487                | E.Probe(E.Prod p, x)=>let
488                    val (p',x')= (rewriteBody (E.Prod p), rewriteBody x)
489                    fun  probeprod([],rest) =
490                            (print "err-Did not find field/Conv"; body)
491                      | probeprod(E.Const c::es,rest)=
492                            (changed:=true;probeprod(es,rest@[E.Const c]))
493                      | probeprod(E.Tensor t::es,rest)=
494                            (changed:=true;probeprod(es,rest@[E.Tensor t]))
495                      | probeprod(E.Krn e::es, rest)=
496                            (changed:=true;probeprod(es, rest@[E.Krn e]))
497                      | probeprod(E.Delta e::es, rest)=
498                            (changed:=true;probeprod(es, rest@[E.Delta e]))
499                      | probeprod(E.Value e::es, rest)=
500                            (changed:=true;probeprod(es, rest@[E.Value e]))
501                      | probeprod(E.Epsilon e::es, rest)=
502                            (changed:=true;probeprod(es, rest@[E.Epsilon e]))
503                      | probeprod(E.Partial e::es, rest)=
504                            (changed:=true;probeprod(es, rest@[E.Partial e]))
505                      | probeprod(E.Field f::es,rest)=
506                            (changed:=true;E.Prod(rest@[E.Probe(E.Field f, x')] @es))
507                      | probeprod(E.Conv f::es,rest)=
508                            (changed:=true;E.Prod(rest@[E.Probe(E.Conv f, x')] @es))
509                      | probeprod(E.Prod p::es , rest)=
510                            (changed:=true;probeprod(p@es,rest))
511                      | probeprod(_,[])=body
512                      | probeprod(e1::es, rest)=let
513                            val e'= rewriteBody(E.Prod(e1::es))
514                            val e''= rewriteBody(E.Probe(e',x'))
515                        in  (changed:=true;E.Prod(rest@[e'']))
516                        end
517                    in (case p'
518                        of E.Prod pro=>probeprod(p,[])
519                        |_=> E.Probe(p',x')
520                        (*end case*))
521                    end
522                    | E.Probe(u,v)=>  (E.Probe(rewriteBody u, rewriteBody v))
523              (*end case*))              (*end case*))
524    
525        fun loop body = let        fun loop body = let
# Line 434  Line 527 
527    
528              in              in
529                if !changed                if !changed
530                  then (changed := false;(*print(P.printbody body');*) print "\n => \n" ;loop body')                  then (changed := false ;loop body')
531                  else body'                  else body'
532              end              end
533                    val z=print "hi"
534                    val u= print(Int.toString( length(params)));
535      val b = loop body      val b = loop body
536      in      in
537      ((Ein.EIN{params=params, index=index, body=b}))                  Ein.EIN{params=params, index=index, body=b}
538      end      end
539  end  end
540    

Legend:
Removed from v.2485  
changed lines
  Added in v.2499

root@smlnj-gforge.cs.uchicago.edu
ViewVC Help
Powered by ViewVC 1.0.0